Overexpression of cathepsin D in malignant melanoma - Zhu, Li; Wada, Maiko; Usagawa, Yuko; Yasukochi, Yumi; Yokoyama, Asuka; Wada, Naoko; Sakamoto, Maiko; Maekawa, Tomoko; Miyazaki, Reiko; Yonenaga, Etsuko; Kiyomatsu, Mari; Murata, Maho; et al. (Fukuoka igaku zasshi = Hukuoka acta medica, 2013)
Cathepsin D is an aspartic lysosomal endopeptidase present in most mammalian cells. Overexpression of cathepsin D is associated with the progression of several human cancers including melanoma. We examined the expression levels of cathepsin D in 20 primary malignant melanomas, 20 metastatic malignant melanomas, 20 benign nevus pigmentosus and 10 normal skin samples in Japanese. In normal skin, granular or dotted pattern of positive staining was observed along the granular layer of epidermis and hair follicle with apparent moderate to strong staining in sebaceous and eccrine glands. The percent positivity and staining intensity of cathepsin D in primary and metastatic malignant melanomas were significantly higher than that of nevus pigmentosus. Moreover, the expression levels of cathepsin D in metastatic malignant melanomas were significantly higher than those of primary malignant melanomas. Data from our and previous reports strongly supports a notion that the upregulation of cathepsin D may be critically involved in the malignant transformation and progression of melanocytic tumors.